Comprehensive school health: teachers' perceptions and implementation of classroom physical activity breaks in US schools. (27th September 2022) - Barcelona, Jeanne; Centeio, Erin; Phillips, Sharon; Gleeson, Dara; Mercier, Kevin; Foley, John; Simonton, Kelly; Garn, Alex
Summary: Modifications to the social–ecological model, such as Whole School, Whole Community, Whole Child (WSCC) frameworks, have been utilized in comprehensive school health interventions. Classroom physical activity breaks are used when implementing whole-of-school approaches. However, the onus to implement classroom physical activity breaks is on school stakeholders. This study aimed to explore teacher and principal perceptions and implementation of physical activity breaks in elementary schools. Further, this study investigated how theoretical factors representative of the social–ecological model and their interactions affect teacher and principal perceptions and utilization of classroom physical activity breaks. Interviews were conducted to understand teacher and principal perceptions and implementation. A total of 12 classroom teachers and five principals participated in semi-structured interviews which were analyzed using constant comparison and deductive analysis to identify relationships and themes coded across the social–ecological and WSCC models. To ensure fidelity individuals that led the professional development ( n = 2) were also interviewed. Three main themes emerged as part of the data analysis: (i) The Connection Between Intrapersonal Knowledge and Interpersonal Professional Development, (ii) Resources, Sharing Means Caring and (iii) The Policy Level Creates Time. Teachers and principals valued knowledge and resources and felt that policy facilitated implementation. Results suggest that classroom physical activity breaks are influenced by multiple factors across varied levels of the social–ecological model. Understanding this relationship can inform future professional development to increase the provision of classroom physical activity breaks among teachers. Lay Summary: Global health statistics suggest that youth health is deteriorating. In response, international and national health organizations have called for school settings to adopt comprehensive school health approaches that provide youth with ample opportunities, such as physical activity across the school day, to improve their health behaviors and instill lifelong healthy habits. This study used the social–ecological model, which considers the interactions between an individual, their community, and the physical, social and political environments, to frame the exploration of how teachers and principals perceive and utilize physical activity breaks in elementary schools. Findings indicate that to foster school health, a comprehensive approach that supports teachers and their interactions while providing resources and policies is needed. Adoption of classroom physical activity breaks begins with teacher knowledge which fosters teacher interaction where best practices are built. Structural supports, including access to resources and the presence of policy, are also critical to sustained implementation because they can reinforce and support teachers' individual and shared use of health-based learning practices across the school day.